Acute Pancreatitis in COVID-19-associated Multisystem Inflammatory Syndrome of Children—A Single Center Experience. Issue 1 (10th February 2022) - Acharyya, Bhaswati C; Dutta, Monideepa; Meur, Saumen; Das, Dhritabrata; Acharyya, Saumyabrata
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: A multisystem inflammatory syndrome in children (MIS-C) was identified as an entity temporally associated with the present COVID-19 pandemic. This inflammatory syndrome affects various organ systems including the gastrointestinal and hepatobiliary systems. The following study was undertaken to primarily detect the fraction of children who had pancreatitis as major organ involvement during the development of MIS-C. The secondary objective was to evaluate their clinical and investigational profile as well as the outcome of management. Methods: A retrospective chart analysis of all children admitted in a tertiary pediatric center from April to December 2020, diagnosed as COVID-19 associated MIS-C, was done. Those presenting with acute pancreatitis were detected and detailed clinical features, investigations, treatments, as well as outcomes, were recorded. Results: A total of 17 children were diagnosed as MIS-C associated with SARS-CoV-2 in the above-mentioned period. Among them, 9 (53%) children had pancreatitis right from the start of the illness; 5 (56%) children with pancreatitis presented with shock. A very high CRP and cardiac involvement were observed in all. A severe reduction of myocardial contractility was associated with poor outcomes. Necrotic pancreatitis was not noted in any of them. A mortality of 22% was documented in this group and a 3-month outcome among those who survived displayed complete resolution of all cardiac as well as pancreatic abnormalities. Conclusion: Acute pancreatitis can be an essential cause of abdominal symptoms in COVID-19-related MIS-C. Pancreatitis may be considered to be one of the parameters in the diagnostic criteria of MIS-C.